2017
DOI: 10.1016/j.apenergy.2017.03.127
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ilmenite as an oxygen carrier for solid-fueled chemical looping combustion

Abstract: Ilmenite ore is one of the promising oxygen carriers (OCs) used for coal-fueled Chemical-Looping Combustion (CLC) for electricity generation and CO 2 capture. However, the low reactivity and natural activation of ilmenite OC are two major constrains impeding its application. This effort is to improve ilmenite OC's performance by introducing a small amount of foreign elements, including alkali or alkaline earth metals (K and Ca) and transition metals (Cu, Mn, and Ni). Coating and re-granulation methods were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Similar activation phenomena also existed for natural ilmenite during the CLC process, and the redox activity of ilmenite was increased during the initial cycles. The results indicated that the activation phenomenon was caused by the improvement of the microstructure for ilmenite in redox reactions.…”
Section: Resultssupporting
confidence: 59%
“…Similar activation phenomena also existed for natural ilmenite during the CLC process, and the redox activity of ilmenite was increased during the initial cycles. The results indicated that the activation phenomenon was caused by the improvement of the microstructure for ilmenite in redox reactions.…”
Section: Resultssupporting
confidence: 59%
“…Moreover, Fe accumulated at the surface accompanied by increased porosity. This process is comprehensively discussed in the literature, especially in the context of ilmenite application in CLC processes. ,, However, as during CLC processes the conversion of the OC normally is higher, the activation during OCAC processes can take longer . Because of this, the outer shell observed is comparably thin.…”
Section: Resultsmentioning
confidence: 99%
“…To prevent the accumulation of ash in the system, it is necessary to evacuate them, but this implies significant losses of the OC . Therefore, the use of low-cost materials, especially solid wastes and natural materials, has been a subject of study by different authors seeking more feasible alternatives in the combustion of solid fuels. …”
Section: Introductionmentioning
confidence: 99%